Central mucoepidermoid carcinoma arising directly from a glandular odontogenic cyst of the mandible: a case report - Satoshi Maruyama; Taisuke Mori; Manabu Yamazaki; Tatsuya Abé; Eijitsu Ryo; Hiroyuki Kano; Go Hasegawa; Jun-ichi Tanuma (BMC, 2021)
Abstract Background Central mucoepidermoid carcinoma (MEC) is a rare salivary gland tumor that affects the jawbone. Glandular odontogenic cyst (GOC) is also a rare odontogenic developmental cyst with glandular differentiation. GOC shares some histological features with central MEC, and a pre-existing GOC can develop into central MEC. Here, we present a rare case of central MEC developed directly from a pre-existing GOC of the mandible. Case presentation A 67-year-old Japanese man presented with a cystic lesion in the right third molar region. Histologically, the biopsy specimen demonstrated both typical findings of a GOC component lined with non-keratinized squamous epithelium and a recognizable component of central MEC consisting of polycystic nests with mucous cells, intermediate cells, and epidermoid cells in the cyst wall. The results from the immunohistochemistry for cytokeratin (CK) profiling demonstrated that, while both central MEC and GOC expressed CKs 7, 14, 18, and 19, CK13 was interestingly exclusively expressed in GOC. Fluorescence in-situ hybridization (FISH) revealed the rearrangement of the Mastermind like (MAML)-2 gene in both the MEC and GOC components. Conclusions Our case suggests that central MEC and GOC may be in the same spectrum of diseases caused by the rearrangement of the MAML-2 gene. However, given that the expression profile of CK13 was completely different between central MEC and GOC, they can be considered as separate tumors. Overall, we demonstrated a rare case in which central MEC may have originated directly from the GOC.